Extended platelet‐rich fibrin - Miron, Richard J.; Pikos, Michael A.; Estrin, Nathan E.; Kobayashi‐Fujioka, Masako; Espinoza, Alan Rene; Basma, Hussein; Zhang, Yufeng (Periodontology 2000, 2024)
Platelet‐rich fibrin (PRF) has been characterized as a regenerative biomaterial that is fully resorbed within a typical 2–3 week period. Very recently, however, a novel heating process was shown to extend the working properties of PRP/PRF from a standard 2–3 week period toward a duration of 4–6 months. Numerous clinicians have now utilized this extended‐PRF (e‐PRF) membrane as a substitute for collagen barrier membranes in various clinical applications, such as guided tissue/bone regeneration. This review article summarizes the scientific work to date on this novel technology, including its current and future applications in periodontology, implant dentistry, orthopedics and facial aesthetics. A systematic review was conducted investigating key terms including “Bio‐Heat,” “albumin gel,” “albumin‐PRF,” “Alb‐PRF,” “extended‐PRF,” “e‐PRF,” “activated plasma albumin gel,” and “APAG” by searching databases such as MEDLINE, EMBASE and PubMed. Findings from preclinical studies demonstrate that following a simple 10‐min heating process, the transformation of the liquid plasma albumin layer into a gel‐like injectable albumin gel extends the resorption properties to at least 4 months according to ISO standard 10 993 (subcutaneous animal model). Several clinical studies have now demonstrated the use of e‐PRF membranes as a replacement for collagen membranes in GTR/GBR procedures, closing lateral windows in sinus grafting procedures, for extraction site management, and as a stable biological membrane during recession coverage procedures. Furthermore, Alb‐PRF may also be injected as a regenerative biological filler that lasts extended periods with advantages in joint injections, osteoarthritis and in the field of facial aesthetics. This article highlights the marked improvement in the stability and degradation properties of the novel Alb‐PRF/e‐PRF technology with its widespread future potential use as a potential replacement for collagen membranes with indications including extraction site management, GBR procedures, lateral sinus window closure, recession coverage among others, and further highlights its use as a biological regenerative filler for joint injections and facial aesthetics. It is hoped that this review will pioneer future opportunities and research development in the field, leading to further progression toward more natural and less costly biomaterials for use in medicine and dentistry.